ANALISIS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA PENINGKATAN PELAYANAN PENDIDIKAN DI SMA NEGERI 4 JAYAPURA - Bethsaba S.M.R Vigowati Kafomay (Universitas Cenderawasih, 2020)
The education budget is a critical aspect to coincide schools operational requirements mainly how to meet the needs for investment, operations, and school personnel (facilities and infrastructure). It serves to protect the community, especially those who still need assistance in striving for their right to get proper education services. The objective of this study is to examine the governance of the School Operational Assistance (BOS) budget in improving education services in Senior High School (SMA) 4 Jayapura. This research used descriptive statistical analysis. Qualitative data is in the form of in-depth interviews with several key informants from the School, consisting of the Education and Teaching Office, the Committee, and the parents/guardians of students as well as school documents/archives in the form of School Profiles and Reports Accountability (K-7). The data collection method used in this study is in-depth interviews and documentation. The results show that most of the school budget used for spending on interaction and processes of education. Also, we find that BOS funds had decreased in the last few years. The evaluation of the BOS funds gained attention from the school principal, and cooperation of the inspectorate of the local government.Keywords: School Operational Assistance, School Income and Expenditure Budget, School performance